Bronchial Toilets in Sepsis Patients Treated in The Intensive Care Unit (ICU): A review On Indications and Complications - Lubis, Andriamuri Primaputra; Irina, Rr Sinta; Karim, T. Abdul (JAI (Jurnal Anestesiologi Indonesia), 2024)
The respiratory system is very important for human life. Its performance determines the quality of life. Physical exercise helps patients suffering from various diseases to build physical fitness, improve respiratory mechanisms, and reduce secretions. It is important to choose the right technique for such patients, using fitness and strength training, breathing exercises, bronchial cleansing. Bronchial clearing aims to remove respiratory tract secretions that contribute to recurrent inflammation and respiratory distress. This is based on the position which facilitates the removal of dense secretions due to the influence of gravity. Pharmacological measures to reduce the secretions in the respiratory tract and facilitate coughing, should be administered prior to drainage. Tracheo-bronchial toilet is a method used to clear mucus and secretions from the airways. The benefits of a tracheo-bronchial toilet include preventing infections such as pneumonia and improving drainage of secretions. Methods used in tracheo-bronchial toilets include temporary naso-tracheal intubation with small tubes, percussion, positioning, and coughing. A tracheotomy can also be performed for lung clearance. Toilet bronchoscopy is a potentially therapeutic intervention to aspirate retained secretions in the endotracheal tube and airway and restore atelectasis.